PELAKSANAAN PERJANJIAN SEWA ALAT BERAT ANTARA PT. VICINDO JAYA MAKMUR DENGAN PT. PACIFIC GLOBAL UTAMA - Fillah Akram Ramadhansyah (PT. Hasba Edukasi Mandiri, 2025)
In the implementation of heavy equipment rental agreements, sometimes there are situations of negligence, namely one of the points above is not fulfilled. Likewise with the heavy equipment rental agreement between PT. VJM with PT. PGU, in implementing the Heavy Equipment Rental Agreement Number 11/PGU-VJM/X/2021, PT. PGU. In this agreement, the rights and obligations of each party involved have been agreed. At PT. VJM operates in the General Constriction and supplier sector. The company provides rental of one of the company's assets, namely heavy equipment. In implementing the heavy equipment rental agreement, PT. VJM uses the principle in the agreement, namely the principle of freedom in contracting. Which means that everyone has the right to get what they want. That in its implementation PT. VJM and PT. PGU uses a written rental agreement because it provides certainty regarding the rights and obligations of the parties making it. A rental agreement made in writing can help the proof process if there is a dispute between the parties who made it, then the rental agreement made in writing can end legally. According to the lessee, the heavy equipment rental agreement of PT. This VJM is not in accordance with the contents of the agreement because there are additional costs incurred by the tenant outside of those stated in the agreement. In the case of default in the implementation of the heavy equipment rental agreement between PT. VJM and PT. PGU, dispute resolution can be pursued through the courts or outside the courts based on the voluntary choice of the disputing parties. If an out-of-court dispute resolution effort is chosen, a lawsuit through the courts can only be pursued if the effort is declared unsuccessful by one or both disputing parties.